APPRAISAL OF ATTITUDE IN ONLINE NEWSPAPER WRITTEN BY FEMALE AND MALE - Pramestika, Miraldha; Mahmud, Murni (ELITERATE : Journal of English Linguistics and Literature Studies, 2024)
This research is entitled "Appraisal of Attitude in Online Newspapers Written by Female and Male". The purpose of this research is to identify different types of attitude sets and explain the attitudes expressed in online newspapers written by female and male. This study's data consists of words, phrases, and sentences that come from online news articles published in 2022 on the CNN International and The Washington Post websites. The descriptive qualitative method was used in this study from Miles, Huberman, and Saldana, also Martin and White's attitude appraisal theory being used. This study focuses on affective attitudes, judgment, and appreciation in online newspaper with a specific topic. According to the findings of this study, female and male writers exhibit three attitude subsystems. The appreciation item is then perceived as dominant. Female and male writers, on the other hand, differ significantly in terms of affect and judgment.Keywords: Appraisal, attitude, newspaper, gender